Analisis Pengaruh Harga Terhadap Keputusan Pembelian Pada Cofeeshop Café In Karawang - Aries Budiman; Nelly Martini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to determine and analyze the effect of price on purchases at coffeeshop cafe.in Karawang. This research method uses descriptive and verification with a quantitative approach. The sample used in this study was 140 respondents. The validity of the data in this study consisted of validity, reliability and classical assumption tests consisting of normality tests. The data analysis used in this research is Simple Regression Analysis. The results of this study are Price and Purchase Decisions have a correlation of 0.89 which means there is a very strong relationship. Price also affects purchasing decisions at the Café.in Karawang cofeeshop where the price variable gives an indication of 89% influencing purchasing decisions and the remaining 11% is influenced by other factors that are not examined